The Shining Path Stravinsky at the Kirov - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2003)
The Shining Path: Stravinsky at the Kirov. PALABRAS CLAVE: Kirov, Les Noces, Le Sacre de printemps, Bronislava Nijinska.
Dentro del apartado "Kirov 2003".